2017
DOI: 10.1021/jacs.7b11157
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Crystallization Kinetics in Quasi Two-Dimensional Perovskite and High Performance Solar Cells

Abstract: Halide perovskites with reduced-dimensionality (e.g., quasi-2D, Q-2D) have promising stability while retaining their high performance as compared to their three-dimensional counterpart. Generally, they are obtained in (A)(A)PbI thin films by adjusting A site cations, however, the underlying crystallization kinetics mechanism is less explored. In this manuscript, we employed ternary cations halides perovskite (BA)(MA,FA)PbI Q-2D perovskites as an archetypal model, to understand the principles that link the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
332
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 360 publications
(353 citation statements)
references
References 43 publications
18
332
0
3
Order By: Relevance
“…The photocurrent density-voltage (J-V) curves of the representative solar cells based on different absorber Table S2 in the Supporting Information. [32,35,36,42] Therefore, further work such as improving the grain size and quality of the films should be able to achieve higher J sc values and PCEs. Note that the average J sc of our solar cells is lower than that in other reports.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The photocurrent density-voltage (J-V) curves of the representative solar cells based on different absorber Table S2 in the Supporting Information. [32,35,36,42] Therefore, further work such as improving the grain size and quality of the films should be able to achieve higher J sc values and PCEs. Note that the average J sc of our solar cells is lower than that in other reports.…”
Section: Resultsmentioning
confidence: 99%
“…[35,46,47] To understand the carrier recombination process in the devices, we measured J sc under different light intensities (I) ranging from 50 to 100 mW cm −2 . [35,46,47] To understand the carrier recombination process in the devices, we measured J sc under different light intensities (I) ranging from 50 to 100 mW cm −2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Studies have shown that cesium (Cs) ions are effective in assisting the crystallization of perovskite because of the entropic stabilization. [13] Studies have shown that perovskites with triple cations (Cs + -FA + -MA + )c ould suppress yellow phase impurities and eliminate halide segregation, compared with binary cations in 3D perovskite-based solar cells. [12] By partially replacing methylammonium (MA + )w ith Cs + ,b oth the grain size and surface quality of 2D perovskite films are effectively improved, resulting in reduced trap state density,s uperior charge-carrier mobility,and improved thermal stability.Zhou et al reported that (formamidinium) FA + incorporation can effectively control BA 2 (MA x FA 1Àx ) 3 Pb 4 I 13 crystallization kinetics,a nd reduces nonradiative recombination centers to acquire high-quality films with al imited non-oriented phase.…”
mentioning
confidence: 99%